(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
As long as a person is able to distinguish between emotional and spiritual needs, this ability will gradually become a characteristic of human behavior. Ibn Sina’s works claim that the external environment around people plays a special role in the formation of man, and that this external environment and people affect not only man’s knowledge of the world, but also the composition of good and bad qualities in his behavior. Today, it is especially important to use the work of the scientist and his psychological views more widely in educating the younger generation.